Exploring Objective Interpretation: The Poetry of Mala Abdul Karim Mudarris in Nami's Tafsir - Hawramani, Abduldaim Maruf; Hussein, Hataw Hassan; Abdul Mohammed, Atta Ali; Mahmood, Chnwr Ali; Abdullah, Namam Kamaran; Abdullah, Sozyar Naji; Abdalla, Shabaz (Journal of Linguistics and Social Sciences, 2024)
In this scholarly exploration, we delve into the distinguished Kurdish scholar Mala Abdulkarim Mudarris, known as "Nami," and his unique contribution to Kurdish literature. Despite his significant poetic accomplishments, Nami never compiled a dedicated collection of his works, making his extensive contributions particularly noteworthy. As the first Kurdish scholar to author a poetry book titled 'Bade w Arwzi Al Zaman,' Nami holds a prominent place in literary history. His multifaceted prowess as a writer and poet is evident in his dedication to both his sacred faith and the nuanced interpretation of the Quran. This discourse unfolds in two chapters, first introducing Mudarris and Nami's exegesis, and then exploring the intricate interplay of poetry within Nami's commentary. Through this endeavor, the study enriches Kurdish literature, enhances Quranic understanding, and establishes a profound link between Islamic faith and the cultural tapestry of Kurdistan.